A Research on the Nature of Mutual Cursing - ÃšÂ©Ã™Â„Ã˜Â§Ã™Â†Ã˜ÂªÃ˜Â±Ã›ÂŒ Ã˜Â®Ã™Â„Ã›ÂŒÃ™Â„ Ã˜Â¢Ã˜Â¨Ã˜Â§Ã˜Â¯, Ã˜Â¹Ã˜Â¨Ã˜Â§Ã˜Â³; Ã˜Â±Ã˜Â¶Ã˜Â§Ã›ÂŒÃ›ÂŒ Ã˜Â²Ã˜Â§Ã˜Â±ÃšÂ†Ã›ÂŒ, Ã™ÂÃ˜Â§Ã˜Â·Ã™Â…Ã™Â‡; Ã˜Â±Ã˜Â¶Ã˜Â§Ã›ÂŒÃ›ÂŒ Ã˜Â²Ã˜Â§Ã˜Â±ÃšÂ†Ã›ÂŒ, Ã˜Â§Ã™Â„Ã™Â‡Ã˜Â§Ã™Â… (Ã™ÂÃ™Â‚Ã™Â‡ Ã™Âˆ Ã˜Â§Ã˜ÂµÃ™ÂˆÃ™Â„)
Mutual cursing (liâÄn) is used in special wording and condition in the presence of a judge in case of manâs claim of the womanâs adultery or in case of rejecting paternity of the child by the husband; in that case the punishment of false accusation of unchastity (qadhf) and adultery (zinÄ) are removed respectively from the man and the woman; and the wife and the husband become unlawful (haram) to one another and would not inherit from each other for ever, etc. Jurists are divided upon the nature of liâÄn. Some have considered it to be attestation, some oath, and some a combination of oath and attestation, and each have come up with evidences for their claim. After examining the evidences of each of the three groups given the differences of oath and attestation with liâÄn and given the specific outcomes resulting from liâÄn, this article concludes that liâÄn is none of the above-mentioned instances; rather, the Exalted God, in case of the husbandâs claim as to his wifeâs adultery, has devised a method under the rubric of liâÄn for eliminating punishment of qadhf from him, which gives rise to special rulings and results. Similarly, rejection of paternity has its special rulings and results. In one respect, liâÄn is an independent event and it is not necessary to be one of oath or attestation or a combination of both so as to say it should have their rulings and results.